Comparación del estado de salud oral en niños de la primera infancia de instituciones con diferentes condiciones socioeconómicas de la ciudad de Cúcuta (2023)
The objective of this study was to compare the oral health status in early childhood children from two institutions with different socioeconomic conditions through a descriptive study, determining the socioeconomic characteristics, oral hygiene habits, and oral health status in early childhood children childhood in the Luis Carlos Galán Sarmiento institutions and the Bolivarian Institute.